Aplicación de la masa madre para la elaboración de pan y muffins con harina de haba - Morales Lima, David Sebastián (2024)
The combination of sourdough and bean flour offers an opportunity for innovation in baking, providing nutritional benefits and a distinctive flavor. The general objective of this research was to elaborate bread using sourdough and fava bean flour by conventional baking methods. The specific objectives included the analysis of the elaboration process, the application of the leaven to selected breads and the sensory evaluation of the resulting products. The methodology employed included a literature review, interviews with professionals in gastronomy and bakery, and experimental tests to adjust the proportions of ingredients and fermentation times. The results indicated that the combination of sourdough and fava bean flour is viable, although it required specific adjustments and the incorporation of other flours, such as quinoa and amaranth, to improve the texture and flavor of the bread. Sensory evaluation revealed a generally positive acceptance, highlighting the bread's flavor and texture. However, aspects such as color and density require optimization to increase acceptance compared to traditional breads. This study concludes that the integration of fava bean flour in bakery products is not only feasible but could also enrich the bakery offer with healthier and protein rich options, reflected in the successful preparation of Pan de Ambato, Pan Chimborazo, glazed Rosquitas and Muffins.